2014
DOI: 10.1161/circulationaha.113.007101
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T Cells Promote the Transition From Hypertrophy to Heart Failure During Chronic Pressure Overload

Abstract: + T-cell subsets (CD8KO). In contrast to CD8KO mice, MHCIIKO mice did not develop ventricular dilation and dysfunction. MHCIIKO mice also displayed very low fibrosis, collagen accumulation, and cross-linking within cardiac tissue. Interestingly, mice with transgenic CD4 + T-cell receptor specific for ovalbumin failed to develop HF and adverse remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
269
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(296 citation statements)
references
References 31 publications
17
269
1
3
Order By: Relevance
“…2016) and that T cells are necessary for cardiac inflammation, hypertrophy, and fibrosis in HF induced by TAC, as T‐cell‐deficient mice are protected from these cardiac responses to pressure overload (Laroumanie et al. 2014; Nevers et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2016) and that T cells are necessary for cardiac inflammation, hypertrophy, and fibrosis in HF induced by TAC, as T‐cell‐deficient mice are protected from these cardiac responses to pressure overload (Laroumanie et al. 2014; Nevers et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that both CD4 + and CD8 + T cells were increased in number in ventricular myocardium and in mediastinal heart draining lymph nodes in pressure-overloaded mice. 102 In recombination activating gene 2 knockout mice, lack of both T and B cells prevented contractile dysfunction, but not cardiac hypertrophy, after TAC operation. The lack of CD4 + T cells in MHC-II knockout mice also prevented pressure overload−induced cardiac remodeling and failure, but the lack of CD8 + T cells did not.…”
Section: Cardiac T Cell-cardiomyocyte Communications In Cardiac Hypermentioning
confidence: 99%
“…Mechanical stretch has been suggested as triggering purinergic signaling in cardiomyocytes, leading to release of fibrogenic growth factors (107). Moreover, T lymphocytes and macrophages have been implicated in activation of resident cardiac fibroblasts following pressure overload (108,109).…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%